Strategies to promote goat research and technology transfer - Lebbie, S.H.B. (Institut de l'Elevage, 2000)
The potential for goat research and Development (R & D) to impact the economic Development of developing countries, particularly in the smallholder sector, cannot be overemphasised. But goat (R & D) has been marginalised in most of these countries, unfortunately. Some of the major underlying reasons have been discussed and suggestions made for future direction to promote goat (R & D).